THE INFLUENCE OF TECHNOLOGY, INNOVATION AND COLLABORATION ON SUSTAINABILITY OF BAMBOO WEAVING CRAFT BUSINESS IN SINGARAJA, BALI PROVINCE - I Made Kartika; Nyoman Dwika Ayu Amrita; Mulia Handayani; Dewa Gede Putra Sedana; I Made Murjana (RADJA PUBLIKA, 2024)
The study aims to reveal the influence of technology, innovation and collaboration on the sustainability of bamboo woven craft businesses in Singaraja, Bali Province. The research method is designed based on a verification approach to strategic management of MSMEs, namely the hypothesis that has been formulated will be verified based on subjective business conditions and business continuity. The variables in this study include: technology, innovation and collaboration in bamboo woven craft businesses as exogenous variables, and business continuity as an endogenous variable. The population of the study was all bamboo woven craft business actors in Sidetapa Village, Tigawarsa Village and Banyuseri Village in the Singaraja area, while the sample size was determined as many as 100 respondents. The research instrument used a structured questionnaire with a simple random sampling technique. The analysis method used to test the research hypothesis is Partial Least Square (PLS) analysis. The findings of the study stated that the technology and collaboration variables had a positive and significant effect on the business sustainability variable, but the innovation variable did not show a significant effect on the sustainability of bamboo woven craft businesses in Singaraja.